2022
DOI: 10.1098/rsos.210696
|View full text |Cite
|
Sign up to set email alerts
|

The hamstrings to quadriceps functional ratio expressed over the full angle-angular velocity range using a limited number of data points

Abstract: The hamstring to quadriceps (H : Q) strength ratio is widely used to identify individuals at risk of sustaining hamstring strain injuries. However, its efficacy is not supported by the current evidence. Current methods for the calculation of the H : Q ratio provide only a one- or two-dimensional ratio, often ignoring fundamental muscle mechanical properties. Based on isokinetic torque measurements of the knee flexors and extensors (0–400° s −1 ) in 25 young, physically active males, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The main outcome of this research demonstrated that when the mean of peaks (Q/H ratio) of all three sports were compared, FR was found to be more in football players followed by cricket and tennis players which was statistically signi cant (Table 1). As muscle strength imbalance around the knee joint has been long considered a risk factor for hamstring strain injury (HSI) and is typically examined with the (Q/H) ratio [21,22], the ndings of this study suggested that all three groups could be at risk of injury since the peak force of Quadriceps was lower than Hamstring. However, the H/Q ratio was highest in the football groups suggesting lower comparative risk.…”
Section: Discussionmentioning
confidence: 84%
“…The main outcome of this research demonstrated that when the mean of peaks (Q/H ratio) of all three sports were compared, FR was found to be more in football players followed by cricket and tennis players which was statistically signi cant (Table 1). As muscle strength imbalance around the knee joint has been long considered a risk factor for hamstring strain injury (HSI) and is typically examined with the (Q/H) ratio [21,22], the ndings of this study suggested that all three groups could be at risk of injury since the peak force of Quadriceps was lower than Hamstring. However, the H/Q ratio was highest in the football groups suggesting lower comparative risk.…”
Section: Discussionmentioning
confidence: 84%
“…While the specific values can vary based on numerous factors (including age, sex, and training status), normative H:Q ratios at slow speeds (like 60°/s) are often around 0.6–0.75 and can decrease to around 0.5 or lower at faster speeds (180–240°/s). A study on football players’ functional hamstring to quadriceps ratio found that H:Q ratios were 0.9, 1.03, and 1.04, respectively, for isokinetic measurements with 60°/s [ 48 ]. Another study on professional male soccer players found that the H:Q conventional ratio mean scores were close to 60% when tested at low to intermediate angular velocities and around 70–80% at fast angular velocities.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on professional male soccer players found that the H:Q conventional ratio mean scores were close to 60% when tested at low to intermediate angular velocities and around 70–80% at fast angular velocities. The H:Q functional ratio mean scores were close to 80% at 60°/s, around 100–130% at intermediate to fast angular velocities, and near or above 130% when angular testing velocities were mixed [ 48 ].…”
Section: Discussionmentioning
confidence: 99%